What drives Chinese overseas M&A investment? Evidence from micro data. Issue 1 (5th July 2021) - Fuest, Clemens; Hugger, Felix; Sultan, Samina; Xing, Jing
Abstract: In recent years Chinese foreign acquisitions have increased significantly. In Europe and the United States, these investments are often criticized. Critics argue that Chinese investors outbid competitors with help from their government, that the acquisitions lead to undesirable technology transfer, or that they may have negative consequences for the employees of the target firm. We use a large deal‐level dataset on cross‐border acquisitions to investigate whether Chinese foreign acquisitions differ from cross‐border investment coming from other countries. We find that relative to non‐Chinese investors, Chinese acquirers indeed appear to be different in some dimensions. They focus on targets with higher debt levels and lower profitability. At the same time, they do not seem to pay more for targets with given characteristics, questioning the view that they are subsidized to outbid other investors. Policy initiatives like the Belt and Road Initiative and Made in China 2025 influence state‐owned but not private Chinese investors, suggesting that geopolitical or technology interests play a role. In the years after the takeover, target companies acquired by Chinese investors exhibit lower growth in capital productivity but a higher growth of employee compensation.